Evidence‐based systems engineering. Issue 3 (14th February 2018) - Hybertson, Duane; Hailegiorghis, Mimi; Griesi, Kenneth; Soeder, Brian; Rouse, William
Abstract: Systems engineering as with many other disciplines has a foundational challenge of using evidence as the basis for decisions that need to be made in support of the engineering and operations of systems. This challenge is compounded by increasing complexity and rates of changes of modern systems and the large amount of data that is available from these systems and their environments. To address these challenges and opportunities, systems engineering needs to modernize and develop new methods, processes, and tools to ensure that best objective evidence is habitually applied. The authors propose a framework, a systematic way of leveraging available evidence to make decisions or solve problems, both in the practice of systems engineering and in its application domains. This framework includes the combining of scientific knowledge with data analytics to produce best evidence, and then applying mediating context factors to the evidence to make SE decisions. Lessons learned from evidence‐based practice in other domains, especially law and medicine, are described and incorporated into evidence‐based systems engineering (EBSE). Finally, this article provides examples of applying EBSE in practice within SE as well as in SE application domains.